Upaya Meningkatkan Hasil Belajar IPS Terpadu Materi Pokok Mengenal Negara-Negara ASEAN pada Siswa Kelas 8 MTs dengan Model Play Based Learning berbantuan Metode Card Matching - Deswati Nasution, Efi (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
This type of research is a classroom action research conducted through two cycles in two months in 2021. Each cycle consists of four stages, namely: planning, implementation/action, observation, and reflection (Siyoto & Sodik, 2015). This study aims to improve the learning outcomes of students in class VIII.2 at MTs N 3 Pekanbaru City in the Integrated Social Studies subject matter of recognizing ASEAN countries through experimental efforts to apply the play-based learning model with the index card match method. The subject of the research was 32 students of class VIII.2 with the object of research was student learning outcomes. Data collection methods are done through observation, questionnaires, and test instruments. The data analysis technique is done by describing or describing the results of the qualitative and quantitative processed data obtained. There are two indicators that indicate the success of the research, namely: 1) Student feedback on the implementation of learning received positive responses from all students reaching 80%; 2) Students who experienced an increase in learning outcomes with a KKM score ≥ 81 as much as 85% of the total number of students. The results of the study concluded, among others: 1) In cycle I, students' learning outcomes increased by achieving 65.6% completeness with an average score of 83.5. In cycle II, learning completeness also experienced a significant rate of increase, reaching 90.6% with an overall student average score of 90; 2) The results of the questionnaire related to the value of student responses during the learning action process carried out resulted in an average value of 42.6 in the agree category. These results conclude that the application of the card matching method can improve learning outcomes and attract their interest so that students can follow the learning well